2021
DOI: 10.1016/j.cej.2020.126786
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of bicarbonate (HCO3−) to acetate and simultaneous heavy metal Cr(VI) removal in photo-assisted microbial electrosynthesis systems combining WO3/MoO3/g-C3N4 heterojunctions and Serratia marcescens electrotroph

Abstract: The removal of the hazardous heavy metal Cr(VI) in water and the simultaneous production of acetate from the reduction of inorganic carbon (HCO3 -) is demonstrated in a photo-assisted microbial electrosynthesis (MES) system incorporating WO3/MoO3/g-C3N4 Z-scheme heterojunctions and Serratia marcescens Q1 electrotroph cathode. The rates of acetate production (6.1 ± 0.3 mg/L/h) and Cr(VI) removal (4.5 ± 0.1 mg/L/h) recorded at a circuital current of 2.8 ± 0.1 A/m 2 were 2.4-fold (acetate production), 1.7-time (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Bittencourt et al (2020) integrated brown algae Laminaria hyperborean with TiO 2 to achieve the reduction of Cr 6+ to Cr 3+ , although its performance was lower than that of the L. hyperborean coated with FeCl 3 . A biocathode was prepared with Serratia marcescens and WO 3 /MoO 3 / g-C 3 N 4 heterojunctions in a BPEC system, which allowed the simultaneous reduction of Cr 6+ and H + , and the produced H 2 was further used for acetate production (Huang et al, 2021). Those results provide a potential strategy for efficient removal of toxic heavy metal from wastewater, along with the simultaneous conversion of inorganic carbon to key block chemicals.…”
Section: Pollution Controlmentioning
confidence: 99%
“…Bittencourt et al (2020) integrated brown algae Laminaria hyperborean with TiO 2 to achieve the reduction of Cr 6+ to Cr 3+ , although its performance was lower than that of the L. hyperborean coated with FeCl 3 . A biocathode was prepared with Serratia marcescens and WO 3 /MoO 3 / g-C 3 N 4 heterojunctions in a BPEC system, which allowed the simultaneous reduction of Cr 6+ and H + , and the produced H 2 was further used for acetate production (Huang et al, 2021). Those results provide a potential strategy for efficient removal of toxic heavy metal from wastewater, along with the simultaneous conversion of inorganic carbon to key block chemicals.…”
Section: Pollution Controlmentioning
confidence: 99%
“…The photocurrent density follows the sequence of PI < AgBr < 0.5-AP. These results indicated that 0.5-AP exhibited evidently high carrier separation efficiency compared with PI and AgBr. Simultaneously, 0.5-AP expresses the minimum Nyquist cycle (Figure b), indicating that the charge transfer resistance of 0.5-AP is the least among the prepared samples. At the same time, Figure c illustrates that when the excitation wavelength is 380 nm, all samples have a strong absorption peak around 480 nm, which is due to the photoinduced electrons and holes recombining. Nevertheless, the PL emission intensity was decreased after AgBr combination with PI, implying enhanced charge separation efficiency. To obtain further evidence for the photoinduced carriers separation rates of the three abovementioned samples, time-resolved photoluminescence was conducted.…”
Section: Resultsmentioning
confidence: 85%
“…[174] Electrotrophs, which contain electroactive membrane proteins, redox mediators, or appendages can also be selected or genetically engineered to better mediate electron transfer from semiconductor to microbes. [168,175] The use of diffusible redox mediators is also typical to facilitate the interelectron transfer. In particular, NAD(P) + , [176] bipyridinium salts [165b,177] (e.g., methyl viologen), rhodium complexes [178] are commonly used as redox mediators in enzymatic PEC systems (Figure 10B).…”
Section: Cocatalystsmentioning
confidence: 99%